Bibliometric Analysis of Project Management: Exploring the Linkages Between Research and Practice - Loso Judijanto; Rosdiana Arief Tang; Said Hamzali; Himawan Sutanto; Sulaiman Mansyur (Westscience Press, 2024)
This study presents a comprehensive bibliometric analysis of project management research to explore its evolution, thematic trends, and the connections between academic contributions and practical applications. Utilizing data from the Scopus database, the analysis spans publications from 2000 to 2024, identifying key contributors, influential institutions, and global collaborative networks. The findings reveal a dynamic shift in project management research from traditional themes such as risk management and cost control to contemporary focuses on sustainability, innovation, and stakeholder engagement. Prominent authors and institutions were identified, with developed countries leading in research output and collaboration. However, growing contributions from developing nations highlight an emerging inclusivity. The study underscores the interdisciplinary and global nature of project management while identifying a persistent gap between academic research and practical implementation. Recommendations for future research include enhancing collaboration between developed and developing regions, focusing on practical applications of emerging themes, and adopting interdisciplinary approaches. This analysis serves as a foundation for advancing project management research to meet evolving global challenges effectively.